Therapeutic tactics for chronic tonsillitis in patients with functional dysphonia (Literature review) - Akhunjonov Dilmurod Makhammadsobirovich; Abdullaeva Nigora Nusratovna (Genius Journals, 2024)
Topicality.The voice plays a huge communicative role in our life, and in the professional activities of people for whom voice and speech are a "tool" of labor, voice formation disorders can lead to temporary or permanent disability. The vocal tract includes three systems: aerodynamic or energy (lungs), vibratory (vocal folds) and resonator (upper and lower resonators). and with the central nervous system in order to form voice and speech [1]. Being part of the resonator part of the vocal apparatus, the palatine tonsils affect the voice and speech. It is assumed that this effect is due to two reasons. First, the palatine tonsils affect the resonance in the vocal tract by volumetric exposure [2]. Secondly, the palatine tonsils can influence resonance along with articulation due to their tissue characteristics [3]. According to modern ideas, chronic tonsillitis is characterized as a multifactorial immunopathological process that can contribute to the development of local and systemic complications with the development of cardiovascular, neuroendocrine, immunological, and metabolic syndromes [4]. In modern clinical practice, up to 80 metatonsillar diseases are known [5]. However, the question of the impact of chronic tonsillitis on the voice function has not yet been finally resolved [6, 7]. Objective: to study the latest literature on therapeutic tactics in chronic tonsillitis in patients with functional dysphonia
Keywords: chronic tonsillitis; functional dysphonias; palatine tonsils